Springer Handbook of Systematic Musicology (Springer Handbooks,, 2018)
The Handbook of Systematic Musicology is trying to reflect this interdisciplinary nature of Systematic Musicology in seven sections. These sections follow the main topics in the field, Musical Acoustics, Signal Processing, Music Psychology, Psychophysics/Psychoacoustics and Music Ethnology while also taking recent research trends into consideration, like Embodied Music Cognition and Media Applications. Other topics, like Music Theory or Philosophy of Music are incorporated in the respective sections.